Biosynthesis, purification and delivery of minicircle DNA for gene therapy - Gaspar, Vítor Manuel Abreu (2018)
The prevalence of numerous diseases which are currently responsible for high mortality rates or that affect people well-being is one of the major challenges faced by nowadays society. To improve general health and population quality of life, tremendous efforts have been focused on speeding up the discovery of innovative pharmaceutics for treatment of particularly complex and incurable pathologies such as cancer. Currently, the generally applied anticancer treatments result only in a slight increase in patient survival rates and additional lifetime without disease recurrence. However, these improvements are often short-lived and are associated with severe systemic toxicity that debilitates patients health during treatment. This fact demonstrates the ineffectiveness and reduced safety of clinically administered therapies, and above all, emphasizes the urging necessity to discover more efficient approaches that can promote a better therapeutic outcome with fewer side-effects. From the numerous anticancer treatments currently under development, those based on nonviral gene transfer with nucleic acid-based pharmaceuticals have a great therapeutic potential since they are currently approved for human use by United States Food and Drug Administration (US-FDA) and European Medidicines Agency (EMA) regulatory agencies, can be produced at industrial scale and are highly versatile. In fact, unlike standard cytotoxic drugs, the original structure of DNA biopharmaceuticals can be precisely engineered to encode multiple, tumor suppressor genes which may simultaneously affect cancer cells proliferation, or induce their destruction without direct damage to healthy tissues. In this context, plasmid DNA (pDNA) gene expression cassettes remain the gold standard biopharmaceuticals for gene therapy. However, despite being a promising tool, the widespread use of standard plasmid vectors is restricted by their short-term activity in vivo. Therefore, to realize the full potential of this therapeutic approach other alternatives for transgene expression in humans must be explored. In this context, a recently upgraded technology based on the use of minimalistic gene expression cassettes devoid of the bacterial backbone, so-termed DNA minicircles, has shown to provide the required biological efficiency. Due to the fact that this is a relatively new technology the parameters of mcDNA production in prokaryotic organisms have not yet been correctly explored. The optimization of this bioprocess assumes a critical importance from a manufacture and therapeutic point of view, since various factors may affect the productivity, final stability and purity of mcDNA preparations. A part from these necessary improvements, mcDNA gene transfer to diseased tissues also remains as one the most rate limiting steps in the translation of these therapies from bench-to-bedside, being necessary as well to improve the currently existing technologies for DNA transfer to eukaryotic cells. Taking this background into account, the main hypothesis of this work was to explore and optimize mcDNA biosynthesis, to screen ligands for purification of these vectors and develop biocompatible polymeric nanocarriers for minicircle gene delivery to different in vitro and in vivo cancer models. As an additional remark to this integrative study, the synthesis of stimuli-responsive delivery systems for co-administration of mcDNA-drug combinations to cancer cells was also investigated. Bioprocess optimization was initially performed by studying and manipulating the amplification of template parental plasmids (PP) in an Escherichia coli strain (ZYCY10P3S2T) genetically modified to produce mcDNA from plasmid templates with high efficiency. During these experiments it was hypothesized that the manipulation of bacterial growth temperature could provide important improvements in the quantity of mcDNA produced in later stages of the process. The obtained results indicated that an increase in bacterial growth temperature maximized the amount of template plasmids per biomass. In addition to this enhancement, a real-time monitoring of the PP–to-mcDNA intramolecular recombination process revealed that the time of mcDNA recovery significantly affects both the final yield and also the presence of residual PP and mini-plasmid (mP) species in minicircle preparations. These important findings demonstrate that maximum productivity and pharmaceutical-grade minicircle batches were obtained at specific time points during the induction phase. Having established optimal bioprocess parameters, the use of novel L-arginine dipeptide ligands for mcDNA biopharmaceuticals isolation or purification was investigated. These dipeptide ligands are particularly interesting as they take advantage of biomimetic interactions that are naturally established between amino acids and DNA in vivo. As a proof-of-concept, mcDNA vectors and PP template plasmids were injected into microfluidic chips containing chemically immobilized dipeptides. The sensitive screening obtained by surface plasmon resonance indicated that by manipulating temperature conditions and buffer type, different ligand-analyte interactions could be established. This dynamic binding-elution profile of mcDNA and PP species, under specific conditions, indicated these peptides could possibly be employed in the development of a platform for biopharmaceuticals isolation or purification. Alongside with these studies, the development of biocompatible nanosized gene delivery systems based on amino acid modified chitosan was explored. For this purpose L-histidine and L-arginine amino acids were selected for chitosan backbone functionalization through a two-step chemical modification. In this study it was proposed that amino acid biocompatible moieties could improve the polymer physicochemical structure and its capacity to condense and deliver genetic material to cancer cells. The chemical modification of chitosan with both amino acid moieties through zero-length crosslinkers was successful and resulted in the development of a novel biofunctionalized material with pH-responsive character and positive charge. These characteristics allowed the formulation of DNA-nanocarriers through attractive electrostatic interactions with model pDNA vectors, under mild conditions. These nanoparticles achieved an improved cellular uptake and higher transgene expression efficiency in cancer cells when compared to their non-modified counterparts. As a further attempt to improve the selectivity of these delivery systems towards target cancer cells, in a subsequent study, the hybrid polymer was chemically grafted with poly(ethylene glycol)-folic acid blocks via Michael type thiol-maleimide coupling. This chemical grafting promoted a selective inclusion of folic acid cell targeting moieties into amino acid modified chitosan. The targeting specificity of the formulated DNA-loaded multifunctional carriers was confirmed in in vitro 2D co-culture models comprised by folic acid positive cancer cells and normal human fibroblasts. In addition, the results obtained in 3D multicellular spheroids indicated that the targeted particles penetrated into these in vitro models of solid tumors and accomplished significant transgene expression. A time-course, high-throughput analysis, performed after nanocarriers containing the p53 tumor suppressor DNA were administered, revealed a reduction in spheroids volume along time, thereby supporting the possible use of this technology for cell-selective gene transfer. From this standpoint, it was hypothesized that polymeric delivery systems could also be used for simultaneous co-delivery of chemotherapeutic drugs and DNA biopharmaceuticals. It was anticipated that such combinatorial approach could provide a superior anticancer effect and contribute for the development of more efficient treatments. To materialize this challenging concept, beyond-state-of-the-art triblock copolymers were chemically synthesized since biofunctional chitosan nanocarriers required complex chemical modifications to co-encapsulate mcDNA and drugs. The new synthetic nanomaterials for co-delivery were produced in an application-oriented, safe-by-design, approach that took into account the necessity to assure materials biocompatibility, biological performance and also the physicochemical properties required for simultaneous encapsulation of drug and genes in a single nanocarrier. The obtained results demonstrate that the triblock copolymers self-assembled into nanosized biocompatible micelles with core-shell structure in aqueous environment and condensed mcDNA vectors with high efficacy. In vivo administration of mcDNA-loaded micelleplexes to solid tumors also originated significant transgene expression, which shows the therapeutic potential of this delivery system. The co-delivery concept was also demonstrated with the simultaneous encapsulation of an anticancer drug (Doxorubicin), and mcDNA, in the micellar carriers. As revealed by confocal microscopy and metabolic assays, the dual-loaded micelleplexes presented significant cellular uptake and cytotoxic activity in cancer cells when compared to free drug. After demonstrating the potential associated with drug-gene co-delivery, the formulation of stimuli-sensitive co-delivery systems was investigated. The production of carriers with dynamic response to precise biological cues was expected to provide a new level of therapeutic efficiency since the release of bioactive molecules could be controlled in a spatiotemporal mode. To explore the manufacture of such “smart” nanomaterials two different approaches based on the formerly developed nanocarriers were explored. In a first study, mcDNA-loaded biofunctionalized chitosan nanocarriers were encapsulated in gas-generating poly(D,L-lactic-co-glycolic acid) (PLGA) biodegradable microspheres, previously loaded with an antitumoral drug and sodium bicarbonate. The assembled nanoparticle-in-microsphere hybrid systems were capable of generating carbon dioxide (CO2) bubbles in acidic environment due to bicarbonate presence. In turn, this gas production originated a rapid disassemble of microspheres shell, and consequent contents release. In vitro, the dual-loaded hybrid carrier demonstrated a higher cytotoxicity in cancer cells when compared to that of free drugs or single drug-loaded microspheres. In addition to this platform, in a second study the cationic block of the triblock copolymers was modified with disulfide linkages to allow a redox-responsive release of mcDNA vectors in intracellular compartments poly(2-ethyl-2-oxazoline)-poly(L-lactic acid)-g-polyethylenimine-disulfide (PEOz-PLA-g-PEI-SS). In this study an affinity chromatography monolith disk immobilized with previously investigated L-arginine dipeptide ligands was used to isolate mcDNA supercoiled isoform. The evaluation of bioreducible micelles in 3D in vitro models and orthotopic in vivo tumors indicated that this system has improved transgene expression efficacy and promotes tumor regression when it is used for co-delivery of Doxorubicin and mcDNA. Overall, the research performed throughout this Doctoral thesis described improvements in mcDNA production process and led to the discovery of potential ligands for the isolation of its supercoiled isoform. The original results obtained during this work provide an important body of knowledge in the applicability of the mcDNA technology at a larger scale. Furthermore, the pre-clinical evaluation performed on newly developed nanomedicines demonstrated that grafting multifunctional moieties, or imprinting a stimuli-sensitive character to nanocarriers has a positive effect on their biological performance. It is important to mention that the future inclusion of one or more tumor suppressor genes in mcDNA vectors may contribute to potentiate their therapeutic effect. In this context, and as a concluding remark, the particularly promising results obtained with the administration of PEOz-PLA-g-PEI-SS dual-loaded and stimuli-sensitive micelles demonstrated that these systems enclose an outstanding potential for medical applications in a foreseeable future.